Occupation, rainfall [videorecording (DVD)] - Sparke, Luke; Ewing, Dan, 1985-; Morrison, Temuera; Gillies, Daniel, 1976- (Saban Films, 2021)
Two years into an intergalactic invasion of Earth, survivors fight back in a desperate ground war. While casualties mount by the day, the resistance, along with some unexpected allies, uncovers a plot that could bring the war to a decisive end.